Post-colonial Berlin? Pieke Biermann's Crime Novels as Globalization Critique - Katrin Sieg (Studies in 20th & 21st Century Literature, 2004)
Set in and around Tempelhof Airport, the crime novel 4,5,6 poses the question whether social, cultural, and economic "globalization" continues and aggravates colonizing practices (as scholars like Miyoshi, Chomsky, and Said have argued), or whether the term describes the social conditions of postcoloniality, beyond superpower domination and the bloc system it created...
Keywords: Tempelhof Airport; crime novel; & quot; 4; 5; 6& quot; social; social globalization; cultural; cultural globalization; economic; economic globalization; colonizing practices; colonize; colonizing; Miyoshi; Chomsky; Said; postcolonialization; superpower; domination; bloc system; Pieke Biermann; Berlin; Post-colonial Berlin; post-colonialization; post colonialization